2011
DOI: 10.25011/cim.v34i3.15192
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of ΔΝp63α in cervical squamous cell carcinoma

Abstract: Reduced expression of ΔΝp63α in cervical squamous cell carcinoma Abstract Purpose: As a member of the p53 family, p63 is considered to be an important di erentiation regulation transcriptional factor, but the roles of p63 in many epithelial tumourigenesis and metastasis processes are still not clear. is study was designed to investigate the expression of p63 and its isoform in normal tissues and squamous cell cancer tissues of uterine cervix, and its signi cance in cancer cell di erentiation.Methods: e express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…It has been previously shown that upregulation of PCNA is closely associated with hrHPV and progressive CIN, but does not predict outcome in cervical cancer 135. P63, which is a member of the p53 gene family, is expressed in the basal and parabasal cells of mature cervical, vaginal, and vulval squamous epithelium, and also in cervical reserve cells at the transformation zone 113,136. It has been shown that MIB-1 may be a useful marker for identification of low-grade CIN lesion with high proliferative index 137.…”
Section: Biomarkers Used In Hiv-associated Cervical Cancer Diagnosis/mentioning
confidence: 99%
“…It has been previously shown that upregulation of PCNA is closely associated with hrHPV and progressive CIN, but does not predict outcome in cervical cancer 135. P63, which is a member of the p53 gene family, is expressed in the basal and parabasal cells of mature cervical, vaginal, and vulval squamous epithelium, and also in cervical reserve cells at the transformation zone 113,136. It has been shown that MIB-1 may be a useful marker for identification of low-grade CIN lesion with high proliferative index 137.…”
Section: Biomarkers Used In Hiv-associated Cervical Cancer Diagnosis/mentioning
confidence: 99%
“…It has been previously reported that the abnormal epithelial differentiation of the cervix contributes to the tumorigenesis of cervical cancer [13,33]. p63, notch1, microRNAs, and ITCH are considered to be the most important regulators of differentiation [12,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that p63 expression was decreased or absent in SCC [13]. In this study, we aim to explore the subcellular localization and expression of ITCH and it alternate substrate, LATS1, in the different stages and grades of cervical dysplasia and SCC, which will illustrate the functions of ITCH and LATS1 during the malignant transformation of cervical cells.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Once cell cycle arrest occurs, most basal cells will enter into terminal di erentiation and die by apoptosis [25]. In epidermal keratinocytes, terminal di erentiation and corni cation is a specialized form of apoptosis [26][27]; thus, the disturbance of normal corni cation through the loss of the ability to di erentiate can lead to ma- lignant squamous cell transformation [28][29]. In this study, GRIM-19 was found to be predominantly expressed in the cytoplasm of the middle layer of the cervix and also in the basal layer, although it was completely absent in the surface layer of the cervix.…”
Section: Grim-19 Expression In Cervical Intraepithelial Neoplasias Anmentioning
confidence: 99%